UNDERSTANDING JAVANESE HARSH EXPRESSIONS AS REFLECTIONS OF CULTURAL NORMS, EMOTIONS, AND SOCIAL RELATIONS - Hendrokumoro, Hendrokumoro; Wijana, I Dewa Putu; Ma'shumah, Nadia Khumairo (LLT Journal: A Journal on Language and Language Teaching, 2025)
Although extensive research on Javanese has focused on politeness, speech levels, and also the preservation of social harmony, studies addressing its harsh words and expressions remain limited. This gap fails to address how Javanese accommodate the expression of conflict, frustration, mockery, as well as other forms of emotional intensity that challenge the idealized image of politeness. The main objective of this study was to investigate the lexicons that constitute harsh words or expressions in Javanese, with particular attention to their sources and the cultural analogies that shape their harsh meanings. Data were generated through the introspective method and literature review and analyzed using Conceptual Metaphor and Dysphemism Theory. The analysis revealed that Javanese harsh words or expressions are grouped into three categories: physical activities, physical states, and body parts or organs, with their usage reflecting two opposite poles: negative, when employed to express conflict, frustration, criticism, or mockery; and neutral, when used playfully among close friends. The findings indicate that the harshness of Javanese expressions is not embedded in the lexical items themselves, but instead arises from the situational and socio-cultural contexts, along with the meanings they convey.